Cumulative Index To Hamadryad Volumes 1–29 (1976–2004) - Das, Indraneil; Genevieve, V. A. Gee (Centre for Herpetology, Madras Crocodile Bank Trust, 2004)
A modest newsletter was published by the Madras Snake Park Trust in May 1976, with the stated purpose “to create and further interest in Indian reptiles and amphibians”. A second one was printed for distribution in December of the same year. The third issue appeared in May 1977, this one cyclostyled. It was from the fourth issue, dated September 1977, that the name Hamadryad appears on the cover.